Functionalized Diphenyl (2-oxochroman-4-yl)phosphonates: Dual Synthetic Approaches, Mechanistic Insights and Exploration of a Promising Anti-lung Cancerous Molecule - Karmakar, Indrajit; Chatterjee, Sudipa; Das, Souvik; Brahmachari, Asanjan; Das, GourabKanti; Choudhuri, Tathagata; Brahmachari, Goutam (Synlett)
We herein disclose a dual synthetic approach involving room temperature and mechanochemical strategies for a new series of substituted diphenyl (2-oxochroman-4-yl)phosphonates. Both methods offer a practical and straightforward synthetic route for such bio-relevant organophosphorus compounds. The salient features of both methods are the metal-free synthesis, mild and energy-efficient reaction conditions, good yields with high chemo- and regioselectivity, avoidance of column chromatographic purification, gram-scale synthetic applicability, and operational simplicity. The DFT study offers mechanistic insights into this transformation. Furthermore, the biological studies of the synthesized organophosphorus compounds explored their possible anticancerous profiles, and among the series, diphenyl (6-(tert-butyl)-2-oxochroman-4-yl)phosphonate (3c) exhibited anti-lung cancer activity in vitro. We herein emphasize that 3c might be considered for pre-clinical evaluation to establish its therapeutic relevance as an anti-cancer agent.